Comparison of Irrigation Penetration into the Apical Part of Canals in Hand and Rotary Instrumentations - M. Khabiri; M. Zare Jahromi; M. Feizianfard; R. Ataee Kachooi (Wolters Kluwer Medknow Publications, 2007)
Introduction: The penetration of irrigating solution to the apical one third of canals and removal of debris are dependent on the final size of the instruments and instrumentation techniques used in the canals. The purpose of this study was to evaluate the effect of final instrument size, on irrigation penetration into the apical part of canals in hand K-file instrumentation versus rotary system of Hero 642.Methods and Materials: The mesiobuccal canals of 48 first mandibular molar teeth were selected for this study. The teeth were divided into 2 groups of 24 in each and the mesiobuccal canals were instrumented by hand K-file or rotary system of Hero 642 at 2 stages. After each stage, a contrast medium was injected into the canals and radiographs were taken by RVG system. The irrigation penetration was measured in radiographs by Diamax software. The data were analyzed using t - student test.Results: This study showed that instrumentation up to # 25 file is not enough for irrigation penetration into the apical area. Also by more flaring the canals, more irrigating solution penetrates into the apical part of canals (P 0 0.001), but the difference between hand and rotary systems was not statistically significant (P > 0.05).Discussion: According to this study, instrumentation up to # 30 file results in better irrigation penetration into the apical area. The flaring of the canals is essential for better cleaning and irrigation of apical area.